Karakteristik Guru Ideal dalam Film Pemenang Oscar Berjudul Good Will Hunting - Putri, Yulita; Al Khoiron, Muhamad Fiqhussunnah; Muna, Faizul; Nurhuda, Abid; Sinta, Dewi; Anugrah, Dena Sri (Lembaga Einstein College (LEC), 2024)
Teachers are at the forefront of developing a young generation with multidisciplinary competence, so certain characteristics are needed, as well as the ideal character of a teacher. These criteria can be known from various sources, one of which is the film Good Will Hunting, which was included in the best film category and won the OSCAR. This research aims to describe the characteristics of the ideal teacher in the Oscar-winning film Good Will Hunting. The method used is a qualitative literature study, then collecting data using the note-taking technique, analyzing it, and finally drawing descriptive conclusions. The results of the research show that the characteristics of the ideal teacher in the Oscar-winning film Good Will Hunting include having a patient character even though the student repeatedly upsets him, having a sense of empathy by trying to understand the student's psychological condition, and placing students as subjects by giving students the freedom to develop accordingly. potential, and finally being able to communicate well by knowing when to be firm, angry, or gentle with students